Barriers and Facilitators to COVID-19 Return to School - Megan L. McElhinny; Joshuaa Allison-Burbank; Abagail Edwards; Shannon Archuleta; Elisha Sneddy; Mariel Tang; Kyann Dedman-Cisco; Kristin Mitchell; Elliot Pablo; Rachel A. Chambers; Emily E. Haroz (SAGE Open)
This study aimed to understand facilitators and barriers to returning to in-person learning for youth, caregivers, and school staff from three communities in the Navajo Nation and the White Mountain Apache Tribe following the 2020 COVID-19-driven school closures. A safe and rapid return to school through effective and acceptable COVID-19 mitigation strategies was vital for students’ social and scholastic development and the resilience of staff and families. We interviewed school staff ( n  = 36), caregivers of youth ages 4 to 16 ( n  = 28), and youth ages 11 to 16 ( n  = 25 from the four communities regarding COVID-19 safety measures, school reopening, and return to in-person learning. Interviews were done by research staff from the same communities and guided by the Theoretical Domains Framework (TDF). A team of local research staff with faculty support from afar, coded interview transcripts using codes based on the TDF and through consensus development of additional emergent codes. Participants found regular COVID-19 testing a suitable alternative to contact tracing and social distancing. While, participants generally acknowledged the safety of testing and vaccinations, they also emphasized the importance of self-determination in adopting these strategies. Protection of family and community were strong motivators for adherence to COVID-19-related safety protocols including engagement in testing or vaccination. All participants were generally motivated to return to in-person learning as virtual learning led to challenges with curricular retention, the provision of academic and non-academic supports, and maintaining social engagement. Virtual learning had effects on caregivers and staff as they took on additional roles amidst virtual learning and pandemic-related demands. Findings from this study are relevant to future pandemic planning and while the findings in the study are highly contextualized, the findings may generalize to other NA communities or other groups who have faced historical maltreatment and ongoing injustices. Maintaining in-person learning is a high priority for stakeholders, and study participants were motivated to participate in additional COVID-19 risk mitigation strategies to return while also protecting more vulnerable people in the community. In many Native American communities, future planning should account for the importance of keeping schools open, while motivating stakeholders to adopt mitigation strategies by emphasizing the greater collective good.